The Art of Storytelling: Its Importance in Video Game Immersion When Paired With Localisation - Mariana Cardoso Ribeiro (2022)
This dissertation intends to explore and validate the importance of storytelling, influenced by the localisation process, and whether this has an impact on players' immersion, thus affecting their experience in the video game. Although these are very well-known areas of expertise that have been studied and developed within the research cosmos, there is still an absence of information combining these topics in a practical study directed towards a specific genre or video game. Through the careful design, development, and application of a study, inspired by grounded theory from various authors with articles or research focused on the addressed topics, such as McKee (1997), Mangiron e O'Hagan (2006), Murray (1997), Aarseth (2012), Felizol (2017), Michailidis et. al (2018), e Vickery et. al (2018), participants reflected on their knowledge of the chosen video game - The Witcher III: Wild Hunt - its genre of RPG/ARPG (role-playing game & action role-playing game), as well as their own gaming habits and acquaintance with the video game world. The first step was a survey, which gathered 283 answers, and ascertained the aforementioned aspects. Here, it was possible to ascertain the number of people who would move on to the next stage of the study, as well as the diversity in knowledge about the area of video games, gaming habits, and linguistic preferences. The next stage, which awaited 126 participants, was the gameplay of the video game in two different localised versions (English and Brazilian-Portuguese) and the completion of a respective questionnaire after each experience. A total of 41 participants, out of 126, finished this step and moved on to the final one of the semi-structured interviews, where more developed and in-depth questions were discussed on different aspects of their experience and the research topics at hand. The results allowed for a set of patterns to be created, which intend to raise awareness of certain aspects that should be taken into consideration in order to enhance and further intensify players' immersion during their gameplay experience. This research aims to contribute with additional information, feedback, and perspective, previously missing, regarding the areas of storytelling, localisation, immersion, and video games, and how they can influence each other, within a study involving a specific genre or video game. This study was developed in the hopes of inspiring and guiding anyone from the gaming business into creating or developing new video game experiences that highlight and perfect the patterns that were developed, as well as fuel further discussion or investigation within the scope of the topics, applied to other video games, languages, or genres, thus encouraging future studies or projects about it.